Pentingnya Strategi Branding Bagi Produk UMKM Pendampingan Di Desa Glonggong Kecamatan Dolopo Kabupaten Madiun - Dian Pratiwi; Mintarti Indartini; Endang Edi Rahayu (Universitas Merdeka Madiun, 2020)
Abstract— The number of MSMEs in Indonesia as of 2016 was 57,895,721 units with a contribution of GDP of 60.34% and absorbing employment of 96.99% with the dominance of micro-enterprises at 98.77% (Barnas, 2016). Behind its large contribution to GDP, MSMEs can be a pillar of a strong economy, but face a pile of obstacles. The problems faced in general and nationally are still around the low quality and standardization of products, low capability and quality of human resources, low ability to improve access to finance, less and minimal product innovation touched by technology, difficult regulation and licensing, difficulties in wider market access and many other obstacles. This was also experienced by SMEs in Glonggong Village, Dolopo Subdistrict, Madiun Regency, where in this village was the center of Tempe Chips craftsmen. Priority there are 3 (three) basic problems faced, namely limited product marketing, Performance Products (product display) that are still very simple, not having a product identity (brand) and capital (not bankable). the solution offered is in the form of socializing the importance of the brand as a product identity, training in the preparation of simple financial reports for MSMEs and strategies to penetrate the broader market through packaging innovation.